2023
DOI: 10.3389/fonc.2023.970187
|View full text |Cite
|
Sign up to set email alerts
|

Protein-energy malnutrition and worse outcomes after major cancer surgery: A nationwide analysis

Abstract: BackgroundProtein-energy malnutrition (PEM) has been recognized as a poor prognostic factor in many clinical issues. However, nationwide population studies concerning the impact of PEM on outcomes after major cancer surgery (MCS) are lacking. We aimed to evaluate the postoperative outcomes associated with PEM following MCS.MethodsBy using the Nationwide Inpatient Sample database, data of patients undergoing MCS including colectomy, cystectomy, esophagectomy, gastrectomy, hysterectomy, lung resection, pancreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Prior data have found increased postoperative complications and costs for other major surgeries. 7,8,[10][11][12] A study using the NIS to assess major cancer surgeries found that protein-energy malnutrition was associated with an increased risk of mortality and major complications. 8 Protein-energy malnutrition was also associated with a higher total cost ($35,814 [95% CI, $22,292-$59,579] vs $16,825 [95% CI, $11,393-$24,164]; P < 0.001) and longer hospital length of stay (14 [9][10][11][12][13][14][15][16][17][18][19][20][21] days vs 4 [2-7] days; P < 0.001), particularly in patients undergoing prostatectomy, hysterectomy, and lung resection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior data have found increased postoperative complications and costs for other major surgeries. 7,8,[10][11][12] A study using the NIS to assess major cancer surgeries found that protein-energy malnutrition was associated with an increased risk of mortality and major complications. 8 Protein-energy malnutrition was also associated with a higher total cost ($35,814 [95% CI, $22,292-$59,579] vs $16,825 [95% CI, $11,393-$24,164]; P < 0.001) and longer hospital length of stay (14 [9][10][11][12][13][14][15][16][17][18][19][20][21] days vs 4 [2-7] days; P < 0.001), particularly in patients undergoing prostatectomy, hysterectomy, and lung resection.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States, liver transplantation rates and the total cost of liver transplantation-related hospitalizations have increased over time, particularly among older adult patients and patients with more comorbidities. 6 Protein-energy malnutrition has been associated with postsurgical complications in many fields, including surgeries for gastrointestinal malignancies 7,8 and cardiac 9,10 and vascular surgeries. 11,12 Malnutrition has been associated with poor postsurgical outcomes among patients undergoing liver transplantation; however, the financial effect of protein-energy malnutrition on liver transplantation has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“… 1 In addition, malnutrition may increase risk of certain clinical outcomes due to compromised immune function, including increased risk of sepsis, heart failure, or poor wound healing. 13 , 14 In this study, the ICD-10 diagnosis of malnutrition was excluded from analyses as a potential risk factor following esophagectomy. This exclusion was due to significant collinearity between underweight status and malnutrition (data not shown), and because malnutrition could not be discerned as a preoperative comorbidity versus a postoperative complication in the NRD.…”
Section: Discussionmentioning
confidence: 99%
“…26 In the hospital setting, malnourished patients are twice as likely as well-nourished patients to receive antibiotics for an infection, have longer lengths of stay, higher rates of hospital readmission, significantly worse surgical outcomes, and higher mortality rates, in addition to increased healthcare costs. 27,28 Restrictive diets can contribute to weight loss, thereby promoting the development of malnutrition, and prolonged avoidance of certain types of foods, such as dairy or animal products, may cause vitamin or mineral deficiencies, if micronutrients are not adequately supplemented. Consequently, restrictive diets carry an inherent risk of worsening rather than improving the prognosis of cancer patients; in extreme cases, unmonitored restrictive diets can even lead to death.…”
Section: The Hidden Risks Of Restrictive Dietsmentioning
confidence: 99%
“…In particular, approximately 10%–20% of patients die as a result of malnutrition rather than cancer 26 . In the hospital setting, malnourished patients are twice as likely as well‐nourished patients to receive antibiotics for an infection, have longer lengths of stay, higher rates of hospital readmission, significantly worse surgical outcomes, and higher mortality rates, in addition to increased healthcare costs 27,28 …”
Section: Introductionmentioning
confidence: 99%